A case study illustrating the use of an attachment video‐feedback intervention strategy. Issue 8 (21st May 2018) - Tarabulsy, George M.; Dubois‐Comtois, Karine; Baudry, Claire; Moss, Ellen; Roberge, Annie; Savage, Laura‐Emilie; Cyr, Chantal; St‐Laurent, Diane; Bernier, Annie
Abstract: Children from high‐risk environments are more likely to experience problems in development. Many difficulties are linked to early experiences in the context of the emerging attachment relationship. Over the past 20 years, our group has collaborated with government agencies to develop and implement an attachment‐based video‐feedback intervention strategy (AVI) that targets parental sensitivity and attachment. This case study presents the manner in which a young mother and her 6‐month‐old son experienced AVI. The study shows how the absence of maternal sensitivity and responsiveness to infant signals, difficulties in helping the child regulate affect, and problems in autonomy support are addressed via eight semi‐structured mentoring visits. Discussion focuses on how AVI may be a helpful addition to primary prevention programs.